Enhanced tunability afforded by aqueous biphasic systems formed by fluorinated ionic liquids and carbohydrates - Ferreira, Ana M.
This work unveils the formation of novel aqueous biphasic systems (ABS) formed by perfluoroalkylsulfonate-based ionic liquids (ILs) and a large number of carbohydrates (monosaccharides, disaccharides and polyols) aiming at establishing more benign alternatives to the salts commonly used. The respective ternary phase diagrams were determined at 298 K. The aptitude of the carbohydrates to induce phase separation closely follows their hydration capability, while the length of the IL cation/anion fluorinated chain also plays a crucial role. Finally, these systems were investigated as liquid-liquid extraction strategies for four food dyes. Single-step extraction efficiencies for the carbohydrate-rich phase up to 94% were obtained. Remarkably and contrarily to the most investigated IL-salt ABS, most dyes preferentially migrate for the most hydrophilic and biocompatible carbohydrate-rich phase - an outstanding advantage when envisaging the products recovery and further use. On the other hand, more hydrophobic dyes preferentially partition to the IL-rich phase, disclosing therefore these novel systems as highly amenable to be tuned by the proper choice of the phase-forming components.